2020
DOI: 10.1038/s41598-020-65906-0
|View full text |Cite
|
Sign up to set email alerts
|

General and feature-based semantic representations in the semantic network

Abstract: How semantic representations are manifest over the brain remains a topic of active debate. A semantic representation may be determined by specific semantic features (e.g. sensorimotor information), or may abstract away from specific features and represent generalized semantic characteristics (general semantic representation). Here we tested whether nodes of the semantic system code for a general semantic representation and/or possess representational spaces linked to particular semantic features. in an fMRi st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 58 publications
6
23
0
Order By: Relevance
“…Previous work investigating the combination of words has emphasised centralised, default mode, semantic systems (Graves et al, 2010;Palliera et al, 2011; for a discussion, see Frankland & Greene, 2020), elements of which are known to contain representations of different categories of objects (Bruffaerts et al, 2013;Devereux et al, 2013;Fairhall & Caramazza, 2013b;Liuzzi et al, 2020). To address whether the combination of concepts across domains continues to rely on distributed category-selective regions or is rather centralised into domain-general semantic systems, we compared the representation based upon single-category sentences to those of combined-category sentences across domain-sensitive ROIs.…”
Section: Combined-category Representations Continue To Rely On Category-selective Representationsmentioning
confidence: 99%
“…Previous work investigating the combination of words has emphasised centralised, default mode, semantic systems (Graves et al, 2010;Palliera et al, 2011; for a discussion, see Frankland & Greene, 2020), elements of which are known to contain representations of different categories of objects (Bruffaerts et al, 2013;Devereux et al, 2013;Fairhall & Caramazza, 2013b;Liuzzi et al, 2020). To address whether the combination of concepts across domains continues to rely on distributed category-selective regions or is rather centralised into domain-general semantic systems, we compared the representation based upon single-category sentences to those of combined-category sentences across domain-sensitive ROIs.…”
Section: Combined-category Representations Continue To Rely On Category-selective Representationsmentioning
confidence: 99%
“…The human capacity to retrieve meaning from words, phrases, and visual objects far exceeds the capacities of other animal species as well as all current state-of-the-art machine learning architectures. Functional magnetic resonance imaging (fMRI) has made it possible to map the brain areas underlying this capacity in the adult brain, showing that semantic information is processed in a distributed fashion across large parts of the cerebral cortex (Humphries et al, 2007; Huth et al, 2012, 2016; Liuzzi et al, 2020; Pulvermüller et al, 2009; Tyler et al, 2003). Most areas of this semantic system act largely amodal, that is, they show similar levels and patterns of activation regardless of whether the sensory input that is being processed comes from the visual domain or from the auditory domain (Deniz et al, 2019; Fairhall & Caramazza, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The representation of single words or concepts has been well studied across the brain's semantic system, using methods both investigating the magnitude of the response of specific voxels (Anderson et al, 2017;Deniz et al, 2019;Fernandino et al, 2015;Huth et al, 2016) and relating the semantic distance between word tokens to the distance in observed neural patterns produced by those words (Bruffaerts et al, 2013;Devereux et al, 2013;Fairhall & Caramazza, 2013;Liuzzi et al, 2020). The semantic system can be characterised as a broadly distributed network of left-lateralized frontal, temporal, parietal, and paralimbic regions that show an increased response to semantically richer stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…A metaanalysis of 120 functional magnetic resonance imaging (fMRI) and positron-emission tomography (PET) studies (Binder et al, 2009) identified seven such brain regions: 1) posterior inferior parietal lobe: angular gyrus (AG) and portions of supramarginal gyrus (SMG), 2) lateral temporal cortex: middle temporal gyrus (MTG) and portions of the inferior temporal gyrus, 3) ventral temporal cortex (VTC): mid-fusiform and adjacent parahippocampal gyrus, 4) dorsomedial prefrontal cortex (dmPFC), 5) inferior frontal gyrus (IFG), 6) ventromedial prefrontal cortex (vmPFC), and 7) the precuneus. Multivariate studies show that the voxel-wise pattern of response within regions of this network are also sensitive to the semantic content of single concepts (Bruffaerts et al, 2013;Devereux et al, 2013;Fairhall & Caramazza, 2013;Liuzzi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%